Distance learning in the time of pandemic as a challenge facing the equal status of the public school - Renata Ernst-Milerska (Studia z Teorii Wychowania)
A public school is an institution for all pupils in a given administrative region. In its actions, it must be guided by the principles of tolerance and social egalitarianism. Social egalitarianism is framed in terms of equal educational opportunities and social justice. The COVID-19 pandemic has forced a significant change in the school practice. Distance learning has become the main form. In this article, we discuss the issue of public school social egalitarianism in the context of the results of the students’ opinion poll on the transformation of traditional forms of education into distance learning.